HAKIKAT METODE DALAM PENDIDIKAN ISLAM - Lathifa Adi Listi; Mohammad Fikri Ramadhani Fauzi; Mukhlisin (Sekolah Tinggi Ilmu Ekonomi Darul Falah Mojokerto, 2023)
The use of Islamic education methods that need to be understood is how aneducator can understand the nature of the method in its relevance to the maingoal of Islamic education, namely the formation of a faithful person who isalways ready to serve Allah SWT. the vision was created in a way that carriedout the process and results of teaching and learning of Islamic law that wassuperior, strong and useful for success and resulted in students' awareness ofcarrying out the rules of Islamic teachings through encouragement techniquesthat led to active student learning ideally. This shows that the function of thePAI method (Islamic religious education) is to direct learning success, makeit easy for students to learn based on a strong desire, and encouragecollaborative efforts in teaching and learning activities between teachers andstudents. This Islamic education learning method will be meaningless if notimplemented in educational practice. The implementation of Islamic education methods in learning includes the selection of effective and efficientteaching methods. In the Qur'an there are many methods that can be appliedto convey God's words to humans, such as the uswatun hasanah method, theqishah method, the amtsal (parable) method, the tarqhib and tarhib (rewardand funishment) methods.